Essentialist Educational Philosophy (Doctrine and Its Influence in the Context of Modern Education) - Gunardi, Ahmad; Hartati, Sry (Yayasan Sembilan Pemuda Indonesia, 2024)
The philosophy of essentialism is a conservative educational philosophy formulated as a critique of progressive educational practices in schools. Essentialists argue that the main function of schools is to convey cultural and historical heritage to the younger generation. Essentialism is not an independent philosophical building, but rather a critique of progressive education. This school of essentialism views that education which is based on the view of flexibility in all its forms can be a source of views that are changing, easy to change, lacking focus, uncertain and unstable.